THE EFFECTIVENESS OF GAMES ON STUDENT’S SPEAKING SKILL AT SECOND GRADE OF ISLAMIC JUNIOR HIGH IN GRESIK - Endah Pangastuti; Muammar Chadafi (JEET, Journal of English Education and Technology, 2020)
The researcher examine the effect of games on oral production competemce at second grade of junior high school in gresik. The reason of this study are low motivation on speaking material and students feel difficult on the material. This study is caried out at Islamic Junior High School in Gresik by 40 students. The researcher uses pre-experimental non-randomized pretest posttest design. The result shows that the average score of pretest is 47,89 and 61,71 for posttest, it means that games is effective strategy on teaching speaking, besides the students have high responds in applying the strategy at learning process.